Employee inspecting hydrochloride rotary furnace at Hercules Hopewell plant - Hercules Incorporated (1940)
General view of an unidentified employee inspecting the Hydrochloride Rotary System at the Hercules Powder Company plant in Hopewell, Virginia. The system was likely used during the production of so-called "chemical cotton," a type of purified cellulose obtained from raw cotton linters. Per notations accompanying the photograph, the open building construction visible in the photograph was designed for ventilation. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Hercules Incorporated; Corporations; Cellulose; Machinery